Teoria da objetificação : aplicabilidades no contexto brasileiro - Bercht, Ana Maria (2018)
This paper prepared as part of the researches conducted by the Research Group Prejudice, Vulnerability and Psychosocial Process of the School of Health Sciences of the Pontifícia Universidade Católica do Rio Grande do Sul – PUCRS, had the goal to evaluate the applicability of objectification theory in Brazilian women. This theory has a social-constructionist view, trying to understand the mental health consequences of being a woman in a society that sexually objectifies the female body. Sexual objectification is a phenomenon derived from s sexist society, there for the feminist analytical category of gender is necessary to comprehend this effects on corporeal and psychological experiences which constitute the subject. The main consequence proposed by the theory of living recurrent objectifying contexts is the internalization of an observer's perspective upon one's own body, leading girls and women to treat themselves, in some level, as objects to be looked at and evaluated. It is suggested that this objectified self is accompanied by other psychological experiences and emotions that lead to psychic suffering, such as habitual body monitoring, appearance anxiety and body shame. The accumulation of these experiences can help explain, at least partially, why certain detrimental outcomes such as depressive (D.D) and eating disorders (D.E) affect more women than men. To evaluate the applicability of this theoretical framework, which has proven to be valid in populations of many countries, we built a survey composed by the Self-Objectification Questionnaire, the Body Surveillance Scale, the Body Shame Scale, the Appearance Anxiety, the Eating Attitudes Test (EAT-26), the Scales of Anxiety, Depression and Stress (DASS-21), the Sociocultural Attitudes Towards Appearance Questionnaire (SATAQ-3) as well as a socio-demographic questionnaire and questions related to beauty practices and changes in appearance. The first four instruments mentioned were translated and evidence of validity and reliability was produced in relation to the original scales.The instrument SATAQ-3, which accesses similar constructs related to the internalization of beauty stereotypes and is validated in Brazil, was used as a validation measure to evaluate the convergence with the translated scales. The survey was made available through the online platform Qualtrics. The participants were women from Rio Grande do Sul, with at least 18 years of age, students from several undergraduate courses. A total sample of 621 was achieved, fulfilling the necessary criteria regarding the number of participants for each item of the adapted scales. For purposes of homogeneity, only the data from women who were students in psychology courses were used to test the proposed model of objectification, culminating in a sample of 371. The initial hypothesis was that higher levels of self-objectification and habitual body monitoring would relate to higher scores on depressive and eating disorders symptomatology scales, mediated by the variables of body shame and appearance anxiety. To test this hypothesis, the Bayesian Networks (BN) method was used. Although classical in the production of probabilistic graphical models, this method had not previously been used for the purposed of objectification theory framework. The main value of this method lies in its exploratory capacity that models the general structure of dependence of multiple variables, generating a graphic with the paths of these relations. Differently from the classic model proposed, our results indicated different paths for the outcomes of depression and eating disorders, where in the first one there was a greater contribution of the appearance anxiety variable while in the second the most significant mediating variable was body shame. Although self-surveillance has shown a direct link to the symptomatology of D.E, it didn't relate to body shame, suggesting that this negative emotion may exist and play an important role in the development of eating disorders even if there is no constant habitual body monitoring. Overall, we believe that this first approach shows that objectification theory can be used to understand some of the experiences of sexual objectification of Brazilian women and their consequences for mental health. Our limitations include a sample of women not diversified in ethnic, regional, economic class and sexual orientation aspects, thus we suggest the expansion of research in this sense as well as a more qualitative deepening to understand other specificities of the Brazilian context that may not have appeared in the present study.